Influence of processing methods on the bioavailability of beta-carotene in selected foods - Benitha Augustine (Department of Home Science, College of Agriculture, 2003)
The study entitled "Influence of processing methods on the bioavai labil ity of 13-carotene in selected foods" was carried out with the objective to envisage the current consumption pattern of 13-carotene rich foods and to assess the influence of selected processing techniques on the bioavailability of 13-carotene. The consumption pattern of carotene rich foods was elucidated by a dietary survey conducted among fifty urban and fifty rural homemakers from Thiruvananthapuram district. Personal profile of the respondents indicated that majority were middle aged Hindu women belonging to nuclear middle income families Most of the families were small sized, with less than five members. The monthly food expenditure pattern indicated that urban families spent more amount on food compared to rural households. With regard to frequency of use of 13-carotene rich foods, locally available green leafy vegetables like agathi, drumstick leaves and chck kurrnanis were consumed more by rural families than urban as these items were available from their homesteads. Amaranth (red and green) though purchased mostly from markets and shops was preferred equally by . households of both areas. Moreover, urban families were found to prefer conventional vegetables like carrot, yam, pumpkin and fruits like dates which arc readily accessible from the markets. Cluster beans a low cost 13- carotene rich vegetable was preferred by rural families. Seasonally available jack fruit and locally available papaya were observed to be more frequently consumed by rural households, while mango, orange and tomato were used in a similar frequency rate by both the groups. The ten commonly consumed 13-carotene rich vegetables identified through survey included green leafy vegetables like agathi, amaranth (red